Benchmarking and calibrating FVS diameter growth predictions with tree-rings and forest inventory data in Sierra Nevada mixed-conifer forests - Eugenia K.L. Batista; Joseph D. Birch; Matthew Dickinson; Chad M. Hoffman; James A. Lutz; Andrew J. Larson; Jessica R. Miesel (Forest Ecology and Management, 2026)

Environment and phytoplankton relative abundances in a hypersaline lake: 27 years in Great Salt Lake, USA and experiments - Gary E. Belovsky; Chad Larson; Younjin Han; Richard Wilson; Hannah J. Appiah-Madson; Heidi Mahon (Aquatic Ecology, 2025)
Over 27 years in Great Salt Lake (GSL: Utah, USA), phytoplankton relative abundances of chlorophytes, diatoms and cyanobacteria varied dramatically (monthly > 90%) of several of the most common GSL phytoplankton (chlorophyte– Dunaliella viridis , diatom– Nitzschia epithemioides , cyanobacterium– Euhalothece sp.). Maximum abundances and growth rates were measured across ranges of temperature (10–30 °C), salinity (30–150 ppt) and nutrients (nitrogen: 0.0–0.64 mg/L, silica:17–51 mg/L) observed within GSL. Experimental results indicated the abundance and growth rate of D. viridis increased as salinity and nitrogen increased and decreased as temperature increased. The abundances and growth rates of N. epithemioides and Euhalothece decreased as salinity increased, and increased as temperature and nitrogen increased, and N. epithemioides increased as silica increased. Observed GSL phytoplankton relative abundances responded to environmental conditions as observed in the experiments, but correlations were weak except for chlorophytes, as diatoms and cyanobacteria relative abundances occasionally increased with unfavorable experimental conditions. The weak correlations between laboratory results and GSL observations could be due to the release of diatoms and cyanobacteria from microbialite biofilms in the lake’s benthos with cold stress and high winds, as a 5–10% release can produce diatom and cyanobacteria phytoplankton relative abundances of 24–48%. This suggests a novel potential link between GSL pelagic and benthic zones.

Stream Co‐Occurrence Networks Depend on Spatial Extent, Environmental Conditions and Organismal Group - William R. Budnick; Joseph L. Mruzek; Chad A. Larson; Thibault Leboucher; Sophia I. Passy (Journal of Biogeography, 2025)
Aim Co‐occurrence networks can be described in terms of topology (i.e., size and connectance) and node degree distribution (NDD). The NDD represents the frequency distribution of nodes (species) with k number of connections (degree). The shape of the NDD, single‐scale, scale‐free (power‐law) or broad‐scale, reveals if there are species with many connections to other species (high‐degree nodes), which may have important ecological functions. However, it remains unknown how spatial extent and environmental conditions impact network topology and the NDD shape and whether these relationships depend on species dispersal capacity. Location Continental United States of America. Taxa Stream diatoms and fish. Methods We constructed landscape windows ranging in spatial extent from 160,000 to 2,560,000 km 2 . For each window, we calculated environmental heterogeneity and median environmental conditions and generated correlation‐based co‐occurrence networks. We evaluated the topology and NDD shape of each network. To each NDD, we fit six statistical models, classified as single‐scale, power‐law or broad‐scale. Contingency table analysis, redundancy analyses and variance partitioning tested the sources of variability in network topology and/or NDD shape. Results The NDDs were almost exclusively fit either by single‐scale + broad‐scale models or broad‐scale models. As spatial extent increased, network size increased, connectance decreased, and the NDD shifted in an organism‐specific manner. In both groups, network responses to spatial extent were attributed primarily to variability in climatic heterogeneity followed by urban development in diatoms. Main Conclusions Spatial extent determined co‐occurrence network properties primarily via climatic and land use factors. Broad‐scale NDDs, indicating the presence of high‐degree nodes, were more common in the well‐dispersed diatoms than in the more poorly dispersing fish. Furthermore, these NDDs increased in frequency with spatial extent and climatic heterogeneity in diatoms but decreased in fish. High‐degree nodes are likely climatic generalists in diatoms but keystone or more dispersive species in fish.

Demographic responses of an extremophile crustacean to environmental factors: Great Salt Lake (Utah, USA) brine shrimp (Artemia franciscana) - Gary E. Belovsky; Chad A. Larson; Heidi K. Mahon; Chad Mellison; Andrea C. Stumpf; Anghy Ramos Valencia (Hydrobiologia, 2025)
Hypersaline Great Salt Lake’s (GSL: Utah, USA) pelagic food web is dominated by the herbivore, Artemia franciscana . Artemia demographic responses (survival, developmental transition, and reproduction) to GSL salinities, temperatures, common phytoplankton and yeast, and food levels were examined by factorial experiment. Survival across developmental stages was best at 90 ppt salinity, and decreased as temperature increased. Transition between life stages was best at 45 ppt salinity, and increased as temperature increased. Food was most important with both survival and transitioning responding similarly to food types and increasing with amount of food. Artemia reproduce in two ways (diapausing cysts – oviparity, live young – ovoviviparity): ovoviviparous and total reproduction were greatest at 90 ppt salinity and 20 °C, while oviparous reproduction was weakly affected by salinity and greatest at 20 °C. Oviparity was greatest at low food availability, while ovoviviparity and total reproduction increased with food availability, so reproduction shifted from oviparity to ovoviviparity as food increased. Maternal effects were observed for cyst hatchability, and ovoviviparous nauplii survival and transitioning to the juvenile stage. Combinations of salinity, temperature, food taxa and food amount strongly affect demography, making single factor studies of limited value. Results explain Artemia abundance in different parts of GSL and among years.

Environmental and Spatial Effects on Co‐Occurrence Network Size and Taxonomic Similarity in Stream Diatoms, Insects and Fish - Joseph L. Mruzek; William R. Budnick; Chad A. Larson; Sophia I. Passy (Global Ecology and Biogeography, 2025)
Aim The influences of environmental and spatial processes on species composition have been at the center of metacommunity ecology. Conversely, the relative importance of these processes for species co‐occurrences and taxonomic similarity has remained poorly understood. We hypothesised that at a subcontinental scale, shared environmental preference would be the major driver of co‐occurrences across species groups. In contrast, co‐occurrences due to shared dispersal history were more likely in dispersal‐limited taxa. Finally, we tested whether taxa co‐occurring due to similar responses to environmental and spatial processes were more taxonomically similar than expected by chance. Location The conterminous United States. Time Period 1993–2019. Major Taxa Studied Stream diatoms, insects and fish. Methods We generated co‐occurrence networks and developed methodology to determine the proportions of nodes and edges explained by pure environment alone (after accounting for space), pure space alone (after accounting for the environment), pure environment and pure space together, and spatially structured environment. Taxonomic similarity of taxa co‐occurring because of environmental and/or spatial controls or because of unmeasured processes was compared to that of a null model. Results Pure environment alone, spatially structured environment, and pure environment and pure space together explained the greatest proportion of nodes and edges in the co‐occurrence networks of diatom species and genera, and insect genera. Conversely, pure environment and pure space together best explained the nodes and edges in the co‐occurrence network of fish species and genera. Co‐occurring taxa were more closely related than the random expectation in all comparisons. Main Conclusions The environment controlled co‐occurrences in all groups, while the influence of space was the strongest in fish, the most dispersal‐limited group in our study. All co‐occurring taxa were more taxonomically related than expected by chance due to environmental or spatial overlap or unaccounted factors.

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

A new perspective on the spatial, environmental, and metacommunity controls of local biodiversity - Sophia I. Passy; Chad A. Larson; Joseph L. Mruzek; William R. Budnick; Thibault Leboucher (Science of The Total Environment, 2024)

On the shape and origins of the freshwater species–area relationship - Sophia I. Passy; Joseph L. Mruzek; William R. Budnick; Thibault Leboucher; Aurélien Jamoneau; Jonathan M. Chase; Janne Soininen; Eric R. Sokol; Juliette Tison‐Rosebery; Annika Vilmi; Jianjun Wang; Chad A. Larson (Ecology, 2023)
The species–area relationship (SAR) has over a 150‐year‐long history in ecology, but how its shape and origins vary across scales and organisms remains incompletely understood. This is the first subcontinental freshwater study to examine both these properties of the SAR in a spatially explicit way across major organismal groups (diatoms, insects, and fish) that differ in body size and dispersal capacity. First, to describe the SAR shape, we evaluated the fit of three commonly used models, logarithmic, power, and Michaelis–Menten. Second, we proposed a hierarchical framework to explain the variability in the SAR shape, captured by the parameters of the SAR model. According to this framework, scale and species group were the top predictors of the SAR shape, climatic factors (heterogeneity and median conditions) represented the second predictor level, and metacommunity properties (intraspecific spatial aggregation, γ‐diversity, and species abundance distribution) the third predictor level. We calculated the SAR as a sample‐based rarefaction curve using 60 streams within landscape windows (scales) in the United States, ranging from 160,000 to 6,760,000 km 2 . First, we found that all models provided good fits ( R 2 ≥ 0.93), but the frequency of the best‐fitting model was strongly dependent on organism, scale, and metacommunity properties. The Michaelis–Menten model was most common in fish, at the largest scales, and at the highest levels of intraspecific spatial aggregation. The power model was most frequent in diatoms and insects, at smaller scales, and in metacommunities with the lowest evenness. The logarithmic model fit best exclusively at the smallest scales and in species‐poor metacommunities, primarily fish. Second, we tested our framework with the parameters of the most broadly used SAR model, the log–log form of the power model, using a structural equation model. This model supported our framework and revealed that the SAR slope was best predicted by scale‐ and organism‐dependent metacommunity properties, particularly spatial aggregation, whereas the intercept responded most strongly to species group and γ‐diversity. Future research should investigate from the perspective of our framework how shifts in metacommunity properties due to climate change may alter the SAR.

Stronger niche than dispersal effects on α‐ and β‐diversity of stream algae, insects, and fish across latitudes in the United States - Joseph L. Mruzek; William R. Budnick; Chad A. Larson; Dinh K. Luc; Sophia I. Passy (Global Ecology and Biogeography, 2022)
Aim Niche and dispersal processes influence biodiversity, but their relative importance along latitude is unclear. We predicted that: (a) niche processes would dominate at high latitudes due to increased climatic stress, consistent with the physiological tolerance hypothesis and the Dobzhansky–MacArthur hypothesis and (b) dispersal limitation would prevail at low latitudes due to narrower niches and smaller range sizes, as postulated by the dispersal–ecological specialization trade‐off hypothesis, the latitude–niche breadth hypothesis, and Rapoport's rule. Location Central United States. Time period 1993–2019. Major taxa studied Stream algae, insects, and fish. Methods We examined the relative effects of environment (climate and physicochemistry) versus space on stream biodiversity in seven latitudinal zones, spanning 19 latitudinal degrees. In each zone, species richness (α‐diversity) was analysed with multiple regression and variance partitioning. Compositional dissimilarity (β‐diversity) within zones was assessed with distance‐based redundancy analysis (dbRDA) and variance partitioning. Results For α‐diversity, latitudinal variability of niche and dispersal processes conformed to our predictions in all three groups, except for dispersal processes in insects. However, the drivers of β‐diversity did not follow our predictions. The latitude–niche breadth hypothesis and Rapoport's rule were weakly supported only in fish. Main conclusions The importance of niche and dispersal processes varied predictably along the latitudinal gradient only for α‐diversity. However, the niche effects were driven mostly by physicochemistry, and the dispersal effects were not always linked with ecological specialization and range size. This suggests that climate‐based biodiversity theories do not have particular relevance for the streams in our study. Niche processes had a greater impact than dispersal processes across species groups and diversity metrics, emphasizing the primary role of the environment.

Current distributions and future climate‐driven changes in diatoms, insects and fish in U.S. streams - Katrina L. Pound; Chad A. Larson; Sophia I. Passy (Global Ecology and Biogeography, 2021)
Aim Biodiversity on Earth is threatened by climate change. Despite the vulnerability of freshwater habitats to human impacts, most climate change projections have focused on terrestrial systems. Here, we examined how the current distributions and biodiversity of stream taxa might change under mitigated, stabilizing and increasing greenhouse gas emissions. Location Conterminous USA. Time period Present day to 2070. Major taxa studied Stream diatoms, insects and fish. Methods We developed species distribution models for 336 freshwater taxa from 1,227 distinct stream localities using water chemistry, watershed and climatic variables. Models based only on climate were used to project changes in the distributions and biodiversity of cold‐ versus warm‐water taxa under representative concentration pathways (RCPs) ranging from 2.6 to 8.5 W/m 2 . Results In all three organismal groups, climate emerged as the strongest predictor of species distributions, providing comparable explanatory power to water chemistry and watershed variables combined. The RCP‐based projections suggested a widespread expansion of warm‐water taxa, outpacing the decline of cold‐water taxa. Consequently, overall species richness would increase, but beta diversity would decrease drastically with the severity of climate change. A closer look at individual taxa and functional guilds revealed that vulnerable cold‐water taxa included: (a) diatom guilds forming the base and bulk of the biofilm; (b) environmentally sensitive insects, characteristic of unimpacted streams; and (c) ecologically and recreationally important salmonids, which were forecast to diminish dramatically in source habitats. Warm‐water fish projected to increase their distributions include bait bucket release minnows and dominant predators. Main conclusions Our results suggest potentially devastating impacts of climate change on stream ecosystems, with the restructuring of diatom, insect and fish communities, diminished distributions of functionally important taxa and widespread expansion of warm‐water taxa, giving rise to biotic homogenization. Given that the magnitude of these biotic shifts depends on the severity of climate change, appropriate current policy decisions are necessary to preserve freshwater ecosystems.

Overwinter survival of crustacean diapausing cysts: Brine shrimp ( Artemia franciscana ) in Great Salt Lake, Utah - Gary E. Belovsky; Clay Perschon; Chad Larson; Chad Mellison; Jennifer Slade; Heidi Mahon; Hannah Appiah‐Madson; John Luft; Ryan Mosley; John Neill; Kyle Stone; Ashley Kijowski; et al. (Limnology and Oceanography, 2019)
Survivability of diapausing (cryptobiotic) life stages over time in nature, beyond maximum observed time for viability, is not well understood. Because these life stages are an adaptation to overcome harsh conditions, survivability over time is assumed to be high. Brine shrimp ( Artemia franciscana ) diapausing eggs (cysts) permit overwinter survival to initiate the population each spring. An experiment was designed to examine overwinter survival of brine shrimp cysts for 17 yr in Great Salt Lake (Utah, U.S.A.). Initial hatchability entering the winter (17.8–78.8%) and overwinter survivability (9.9–65.9%) of cysts varied dramatically among years. Better maternal nutrition increased initial hatchability. Overwinter survival of cysts decreased in part because some cysts hatch when it is too cold for the hatchlings to feed (0.8–39.4% among years), so they starve. However, overwinter cyst survival decreases the most with warmer waters in winter, and with better maternal nutrition, as both factors lead to diapause being easier to break. Annual variation in initial hatchability and survival is shown to be important to Great Salt Lake brine shrimp populations. Therefore, cryptobiotic life‐stage ecology needs to be better understood, as these life stages may have highly variable hatchability and survivability with normal environmental stresses.

Niche dimensionality and herbivory control stream algal biomass via shifts in guild composition, richness, and evenness - Sophia I. Passy; Chad A. Larson (Ecology, 2019)
We developed a framework for the hierarchical pathways of bottom‐up (niche dimensionality) and top‐down control (herbivory) on biomass of stream algae via changes in guild composition (relative abundance of low profile, high profile, and motile guilds), species richness, and evenness. We further tested (1) the contrasting predictions of resource competition theory vs. the benthic model of coexistence on how the number of added nutrients constrains species richness, (2) the relationship between species richness and evenness, and (3) the biodiversity–ecosystem‐function paradigm. Implementing a combination of field and lab experiments that manipulated for the first time in benthic algae herbivory and/or niche dimensionality, i.e., the number of added nutrients ( NAN ), including nitrogen, phosphorus, iron, and manganese, we made the following discoveries. First, important predictors of guild composition were herbivory (field) and NAN (lab); of richness, NAN (field) and NAN and guild composition (lab); of evenness, guild composition (field and lab) and herbivory (field); and of biomass, guild composition, NAN , and richness + evenness (field and lab). Herbivory increased the proportions of the low profile and motile guilds but decreased the proportion of the high profile guild. In the absence of grazing, greater proportions of the high profile guild resulted in elevated richness and biomass but diminished evenness, whereas in the presence of grazing, these relationships generally disappeared. Second, both experiments confirmed the prediction of the benthic model that species richness increases with NAN , a pattern inconsistent with resource competition theory. Third, supplementation with manganese and/or iron increased algal richness, indicating that micronutrients, which have generally been overlooked in stream ecology, added dimensions to the algal niche. Fourth, the richness–evenness relationship, observed only in the absence of herbivory, depended on the size of the species pool. It was positive at richness lower than 49 species (lab), implying complementarity and facilitation, while at higher richness (field and lab), this relationship was negative, consistent with negative interspecific interactions. Finally, the greater dependence of biomass production on guild composition and NAN than on richness and evenness suggests that more comprehensive, environmentally explicit, and trait‐based approaches are necessary for the study of the biodiversity–ecosystem‐function paradigm.

A Large-Scale, Multiagency Approach to Defining a Reference Network for Pacific Northwest Streams - Stephanie Miller; Peter Eldred; Ariel Muldoon; Kara Anlauf-Dunn; Charlie Stein; Shannon Hubler; Lesley Merrick; Nick Haxton; Chad Larson; Andrew Rehn; Peter Ode; Jake Vander Laan (Environmental Management, 2016)

Genesis of the post-caldera eastern Upper Basin Member rhyolites, Yellowstone, WY: from volcanic stratigraphy, geochemistry, and radiogenic isotope modeling - Chad J. Pritchard; Peter B. Larson (Contributions to Mineralogy and Petrology, 2012)

Enhancing Agriculture?s Potential to Sequester Carbon: A Framework to Estimate Incentive Levels for Reduced Tillage - Daniel G. De La Torre Ugarte; Chad M. Hellwinckel; James A. Larson (Environmental Management, 2004)

MHC class I-like genes in cattle, MHCLA, with similarity to genes encoding NK cell stimulatory ligands - Joshua H. Larson; Mark J. Rebeiz; Chad M. Stiening; Ryan L. Windish; Jonathan E. Beever; Harris A. Lewin (Immunogenetics, 2003)